KOMPOSISI VEGETASI SEMAK PADA DUA TIPE “LAND USE” DI DESA PANGALASIANG KECAMATAN SOJOL KABUPATEN DONGGALA SULAWESI TENGAH - Faida Faida; Samsurizal M Sulaiman; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2017)
The research entitled ‘’Composition of shrubs vegetation in Two (2) Land Use types at the Pangalasiang Village, Donggala Regency of Central Sulawesi’’ was conducted from April to October 2015. The aim was to know the composition of shrubs vegetation in two land use types at Pangalasiang Village, Donggala Regency of Central Sulawesi. The types of this research is exploratory survey research by using the establishment of a single plot (50 × 50 m) followed by subplot (5 × 5 m) were placed on regular basis (systematic). The result of this research showed that there were fiveteen (15) species of shrubs plant in the ex ore mining land and twenty three (23) species in natural forest. In the ex ore mining land, the highest (INP) 36,15% refers to Stachytarpheta jamaicensis (L) Vahl. (Verbenaceae) and the highest (INP) 21,02% in natural forest was belong to Ageratum conyzoides L. (Asteraceae). The similarity index between two land use types was 82,92%.